Gene expression of the IGF pathway family distinguishes subsets of gastrointestinal stromal tumors wild type for KIT and PDGFRA. (18th January 2013) - Beadling, Carol; Patterson, Janice; Justusson, Emily; Nelson, Dylan; Pantaleo, Maria A.; Hornick, Jason L.; Chacón, Matias; Corless, Christopher L.; Heinrich, Michael C.
Abstract Gastrointestinal stromal tumors (GISTs) arise from the interstitial cells of Cajal (ICCs) and are the most common mesenchymal neoplasm of the gastrointestinal tract. While the majority of GISTs harbor activating mutations in either the v‐kit Hardy‐Zuckerman feline sarcoma viral oncogene homolog (KIT) or platelet‐derived growth factor receptor alpha (PDGFRA) tyrosine kinases, approximately 10–15% of adult GISTs and 85% of pediatric GISTs lack such mutations. These "wild‐type" GISTs have been reported to express high levels of the insulin‐like growth factor 1 receptor (IGF1R), and IGF1R‐targeted therapy of wild‐type GISTs is being evaluated in clinical trials. However, it is not clear that all wild‐type GISTs express IGF1R, because studies to date have predominantly focused on a particular subtype of gastric wild‐type GIST that is deficient in the mitochondrial succinate dehydrogenase (SDH) complex. This study of a series of 136 GISTs, including 72 wild‐type specimens, was therefore undertaken to further characterize wild‐type GIST subtypes based on the relative expression of transcripts encoding IGF1R. Additional transcripts relevant to GIST biology were also evaluated, including members of the IGF‐signaling pathway (IGF1, IGF2, and insulin receptor [INSR]), neural markers (CDH2[CDH: Cadherin], neurofilament, light polypeptide, LHX2 [LHX: LIM homeobox], and KIRREL3 [KIRREL: kin of IRRE like]), KIT, PDGFRA, CD34, and HIF1A. Succinate dehydrogenase complex, subunit B protein expression was also assessed as a measure of SDH complex integrity. In addition to the previously described SDH‐deficient, IGF1Rhigh wild‐type GISTs, other SDH‐intact wild‐type subpopulations were defined by high relative expression of IGF1R, neural markers, IGF1 and INSR, or low IGF1R coupled with high IGF2. These results underscore the complexity and heterogeneity of wild‐type GISTs that will need to be factored into molecularly‐targeted therapeutic strategies.